The identity of Hamilton’s Ticto Barb, Pethia ticto (Teleostei: Cyprinidae) - Katwate, Unmesh; Raghavan, Rajeev; Dahanukar, Neelesh (Zootaxa, 2015)
While describing the fishes of Ganges, Hamilton described Cyprinus ticto (now allocated to Pethia) from south-eastern parts of Bengal. The unavailability of type material and insufficient diagnostic characters in the original description resulted in ambiguities in the identity of this species. In this paper, we clarify the identity of P. ticto through an integrative-taxonomic approach. Pethia ticto can be distinguished from all other known species of the genus by a combination of characters that includes an abbreviated lateral line with 6–12 pored scales; 23–26 scales in lateral-scale row; 9 predorsal scales; ½4/1/3½–4 scales in transverse series; and a pigmentation pattern that includes a small black humeral spot covering the third and fourth lateral-line scales, a prominent spot on the caudal peduncle on the 16th–19th scales of the lateral-line scale row, and two rows of black spots scattered on the dorsal fin.